Phytotherapy in primary health care - Gisele Damian Antonio; Charles Dalcanele Tesser; Rodrigo Otavio Moretti-Pires (Universidade de São Paulo, 2014)
OBJECTIVE To characterize the integration of phytotherapy in primary health care in Brazil. METHODS Journal articles and theses and dissertations were searched for in the following databases: SciELO, Lilacs, PubMed, Scopus, Web of Science and Theses Portal Capes, between January 1988 and March 2013. We analyzed 53 original studies on actions, programs, acceptance and use of phytotherapy and medicinal plants in the Brazilian Unified Health System. Bibliometric data, characteristics of the actions/programs, places and subjects involved and type and focus of the selected studies were analyzed. RESULTS Between 2003 and 2013, there was an increase in publications in different areas of knowledge, compared with the 1990-2002 period. The objectives and actions of programs involving the integration of phytotherapy into primary health care varied: including other treatment options, reduce costs, reviving traditional knowledge, preserving biodiversity, promoting social development and stimulating inter-sectorial actions. CONCLUSIONS Over the past 25 years, there was a small increase in scientific production on actions/programs developed in primary care. Including phytotherapy in primary care services encourages interaction between health care users and professionals. It also contributes to the socialization of scientific research and the development of a critical vision about the use of phytotherapy and plant medicine, not only on the part of professionals but also of the population.